Pengaruh Green accounting dan Kinerja Lingkungan terhadap Kinerja Keuangan: Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI periode 2019-2023 - Husna, Imalatul; Helmayunita, Nayang; Fitra, Halkadri (Jurnal Eksplorasi Akuntansi, 2025)
The aim of this research is to examine the impact of the implementation of Green Accounting and Environmental Performance on the Financial Performance of Companies in the mining sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research used the multiple linear regression method with the assistance of SPSS software. The research sample was selected using a purposive sampling technique; from 46 companies in the population, 21 companies were chosen as samples. The results showed that the implementation of Green Accounting negatively affects the financial performance of companies (Tobin's Q). Meanwhile, Environmental Performance has no effect on the Financial Performance of Companies.